2002
DOI: 10.1073/pnas.192569699
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Estrogen receptor-interacting protein that modulates its nongenomic activity-crosstalk with Src/Erk phosphorylation cascade

Abstract: Numerous studies have demonstrated that estrogens induce rapid and transient activation of the Src͞Erk phosphorylation cascade. Activation of this cascade triggers vital cellular functions including cell proliferation and differentiation. However, the details of the molecular mechanism of this process remain to be elucidated. We have identified a previously uncharacterized nuclear receptor-interacting protein designated as modulator of nongenomic activity of estrogen receptor (MNAR). Here we show that MNAR mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
314
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(332 citation statements)
references
References 37 publications
11
314
2
5
Order By: Relevance
“…ERa and c-Src bind in a protein complex that has been proposed to involve other proteins such as modulator of nongenomic activity of ER and phosphatidylinositol 3-kinase (16,27,28). Our studies showed hormone-independent interactions between ERa and c-Src that were not altered by estrogen or the K303R-ERa mutation.…”
Section: Discussionmentioning
confidence: 50%
“…ERa and c-Src bind in a protein complex that has been proposed to involve other proteins such as modulator of nongenomic activity of ER and phosphatidylinositol 3-kinase (16,27,28). Our studies showed hormone-independent interactions between ERa and c-Src that were not altered by estrogen or the K303R-ERa mutation.…”
Section: Discussionmentioning
confidence: 50%
“…In recent years, much evidence has shown that in multiple cell types under different experimental conditions, steroid receptors directly interact with several signaling effectors and trigger various biological effects. In addition to Src, these effectors include calmodulin (Castoria et al, 1988), the regulatory subunit of the phosphoinositide 3-kinase, p85a (Simoncini et al, 2000;Castoria et al, 2001), Shc (Song et al, 2002), modulator of non genomic activity of receptor (Wong et al, 2002), protein kinase Cz (Castoria et al, 2004), EGF receptor (Marquez et al, 2001;Migliaccio et al, 2005), and many other signaling or signaling-related proteins. Therefore, approaches similar to those followed in this report, that is, recognition of new receptor/signaling effector interactions and identification of new inhibitors of such interactions, could enable us to specifically inhibit different hormone actions mediated by signal transducing pathways in multiple cell types and in different pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms for hormone therapy resistance remains elusive, recent studies suggest the presence of alternative signaling pathways that activate ER may account for hormonal therapy resistance (19,44,45). Growth factor -mediated phosphorylation of ER and ER coregulatory proteins have been shown to have a role in tamoxifen resistance (15).…”
Section: Discussionmentioning
confidence: 99%
“…PELP1 [proline-rich, glutamic acid -rich, and leucine-rich protein-1; also termed modulator of nongenomic actions of ER (MNAR)] is a recently identified ER coregulator (18,19). PELP1 is a unique coactivator that plays an important role in both the genomic and nongenomic actions of the ER (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation